Local resources and global competitiveness: Andalusia virgin olive oil exports - E. Moral Pajares; José Domingo Sánchez Martínez; A. Mozas Moral; E. Bernal Jurado; M.j. Medina Viruel (Boletín de la Asociación de Geógrafos Españoles)
Texto resumen.